Good vibrations: Itch induction by whole body vibration exercise without the need of a pruritogen. Issue 12 (9th October 2018) - Mueller, Simon; Fischer, Marilena; Herger, Simon; Nüesch, Corina; Egloff, Christian; Itin, Peter; Cajacob, Lucian; Brandt, Oliver; Mündermann, Annegret
Abstract: Mechanically induced itch is an important cofactor in many patients with chronic itch. However, studying mechanical itch in a controlled environment is challenging because it is difficult to evoke. We investigated the use of whole body vibration (WBV) exercise, a training method used for musculoskeletal rehabilitation, to experimentally evoke mechanical itch. Mild to severe itch ascending from the soles to the groins was evoked in 16 of 20 healthy participants. We observed a characteristic on/off itch crescendo pattern reflecting the alternating intervals of vibration and no vibration. Wheals or an angioedema was absent, and serum mast cell tryptase was not increased by the exercise. Participants described the evoked sensation primarily as "itching" with some nociceptive components. Itch intensity correlated with the intensity of a concomitant erythema ( R  = 0.45, P  = 0.043) and with the rise in skin temperature ( R  = 0.54, P  = 0.017). Hence, WBV can be used as an easily applicable, noninvasive, investigator‐ and user‐friendly framework for studying mechanical itch. Moreover, WBV allows to "switch itch on and off" rapidly and to simultaneously study interactions between itch, skin blood flow and skin temperature.